Medieval marriage sermons mass communication in a culture without print - D'Avray, D. L. (Oxford University Press, 2001)
This text reveals what a number of famous preachers actually taught about marriage. It looks at the close connection between marriage symbolism and social, cultural, and legal realities in the 13th century, and assesses the impact of this preaching.